Miraculous response : doing popular religion in contemporary China - Chau, Adam Yuet (Stanford University Press, 2006)
This book-length ethnography of the revival of a popular religious temple in contemporary rural China examines the organizational and cultural logics that inform the staging of popular religious activities. It also explores the politics of the religious revival, detailing the relationships of village-level local activists and local state agents wtih temple associations and temple bosses. Shedding light on shifting state-society relationships in the reform era, this book is of interest to scholars and students in Asian Studies, the social sciences, and religious and ritual studies.